The Ether and its Properties. Photons and Light Emitters in Biquaternionic Presentation - Alexeyeva, L. A., (European Journal of Applied Sciences, 2023)
Here the ether equation in a biquaternionic representation has been presented which is generalization of Maxwell equations in algebra of biquaternions. We consider the ether as electro-gravimagnetic (EGM) field, which is described by the biquaternion of the intensity of EGM field. Its scalar part is called the ether density. The vector part, by construction, describes the intensity of electric and gravimagnetic fields. The ether equation is the biquaternionic wave (biwave) equation which expresses EGM charges and currents through the bigradient of EGM field intensity. Monochromatic solutions of these equations are constructed on the basis of which biquaternionic representations of photons are presented. Free ether waves are considered. It is shown that they and photon biquaternions contain a gravitational component, which determines the light pressure. The various light emitters (ball, spherical, ring, circular pulsars) are considered and their biquaternions are constructed in analytical form.